Identification of Degradation Pathway of Vinyl Acetate Using Bacterial Isolate V2 and Characterization of The Involved Enzymes - Soenarko, Bambang; Sulistinah, Nunik; Nieder, Maria; Meyer, Ortwin (BRIN, 2005)
Vinyl acetate is a toxic substance, but has a high commercial value. In this study we show that vinyl acetate is subject to microbial degradation at rates of up to 6.38 and 1 mmol 1 per g (dry weight) under aerobic and anaerobic conditions, respectively. It was hydrolyzed by bacterium V2 to ethanol, acetaldehyde and acetate. The enzymes involved in the metabolism of vinyl acetate were vinyl acetate esterase, aldehyde dehydrogenase, and alcohol dehydrogenase, which localized in the cytoplasmic fraction. The Km values of vinyl acetate esterase and alcohol dehydrogenase were 6.13 mM and 0.24 mM. respectively. Vinyl acetate esterase hydrolyzed the ester to acetate and vinyl alcohol. The latter isomerized spontaneously to acetaldehyde and was then converted to acetate. The acetaldehyde was disproportionated into ethanol and acetate. The acetate was then converted to acetyl coenzyme A and oxidized through the tricarboxylic acid cycle and the glyoxylate bypass.